Prescription of antibacterials: Knowledge of academic teachers in the Dentistry course (Research, Society and Development, 2020)
Faced with bacterial infections, the dentist is able to prescribe antibacterials for the patient, as long as there is information about the causative agent of the infection and the prescribed drug. In view of this, the objective of the present study was to analyze the knowledge of undergraduate dentistry students at a private college in the Bahian Recôncavo about the prescription of antibacterials. It is a descriptive research, with a qualitative-quantitative approach. One hundred and fifty-nine students from the 4th to the 10th semester participated in the survey, with the majority of students (50.9%) saying that they had already prescribed antibacterials and felt safe to carry out the prescription (58.4%). However, in relation to the rules and mandatory elements that must be included in a prescription, 54.7% of the students stated that they carry out this type of prescription with the absence of elements that would validate the prescription. Demonstrating that it is still necessary for academics to deepen their knowledge about a correct prescription. Regarding the main indications for the use of this drug, measures to avoid bacterial resistance and about antibacterial prophylaxis, it was observed that the students' knowledge is satisfactory, since most answered the questions correctly.